CMOS curvature-corrected voltage reference - Hon, Yau Kin. (2008)
A low voltage curvature-correction band-gap voltage reference is designed and fabricated using IME's 0.8um standard CMOS process. A first-order and a curvature voltage source are used to compensate the base emitter voltage, which has a negative temperature coefficient. It provides an accurate 1.25 V output voltage over a power supply range from 2.4 V to 3.6V. Such a design is suitable for two-battery portable applications. The whole design is divided into several functional blocks and each block is layed out separately in a standard height manner so that each functional block could be reused easily in other designs. Most of the functional blocks have been characterized, and closely matched the simulation results.